Design and Development of an Automatic Angklung Robot Based on Microcontroller - Wicaksono, Agung Rizaldi; Subur, Joko; Taufiqurrohman, Muhammad (Muhammadiyah University, Sidoarjo, 2023)
The angklung is a traditional musical instrument from West Java, Indonesia. It can be played both individually and in groups. Playing the angklung requires precision in terms of tempo, rhythm, pitch, and beats to ensure that the music aligns with the intended song and is enjoyable to listen to. Therefore, not everyone can play the angklung, as it demands skill to achieve the right tempo, pitch, rhythm, and beats. To address this issue, a solution was developed, which involved creating a system and device capable of playing the angklung automatically. In this research, a system was designed to move the angklung automatically, simulating a robot, and it is referred to as the